An updated chronology and paleoenvironmental background for the Paleolithic Loufangzi site, North China. Issue 152 (March 2021) - Peng, Wei; Huang, Xiaozhong; Storozum, Michael J.; Fan, Yuxin; Zhang, Hucai
Abstract: The relationship between the environment and human activities during Marine Isotope Stage (MIS) 4 is important for understanding the origins of modern humans ( Homo sapiens ) in East Asia, an area where various hypotheses of human origins have been vigorously debated over the past three decades. Unfortunately, only a handful of Paleolithic sites date to MIS 4 in East Asia, hampering our understanding of how environmental changes affected human activities during this time period. Here, we used stratigraphic correlation analysis and optically stimulated luminescence to date the Loufangzi site, an important Paleolithic site in North China that has had an unreliable chronology. Pollen analysis, grain size, and magnetic susceptibility were also used to reconstruct environmental conditions at the Loufangzi site area. Our results show that (1) the age of the upper culture layer of the Loufangzi site is bracketed between ∼70 ka and ∼60 ka and dates to MIS 4 and (2) the regional vegetation from MIS 5 to MIS 4 to MIS 3 was mainly dominated by forest steppe, desert steppe/desert, and steppe, respectively, indicating harsh environmental conditions during MIS 4. Combined with the discovery of Mousterian-like scrapers in the upper culture layer of MIS 4, our results challenge the view that the area was unsuitable for human survival during the Last Glacial period and instead suggest that humans used new technologies to increase their resilience to the cooling climate.